2013
DOI: 10.1096/fj.13-230904
|View full text |Cite
|
Sign up to set email alerts
|

Human telomerase reverse transcriptase regulates MMP expression independently of telomerase activity via NF‐κB‐dependent transcription

Abstract: Telomerase plays a pivotal role in the pathology of aging and cancer by controlling telomere length and integrity. However, accumulating evidence indicates that telomerase reverse transcriptase may have fundamental biological functions independent of its enzymatic activity in telomere maintenance. In this study, the ectopic expression of human telomerase reverse transcriptase (hTERT) and its catalytic mutant hTERT K626A induced cancer cell invasion accompanied by the up-regulation of the metalloproteinases (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 37 publications
5
110
0
1
Order By: Relevance
“…Ectopic expression of TERT and its catalytic mutant TERT K626A induced cancer cell invasion, MMP 9 mRNA expression and promoter activity in an NF-κB-dependent manner, regulating several target genes of this signalling pathway (Ding et al 2013).…”
Section: Role Of Tert In Proliferation Invasion and Tumourigenesismentioning
confidence: 98%
See 1 more Smart Citation
“…Ectopic expression of TERT and its catalytic mutant TERT K626A induced cancer cell invasion, MMP 9 mRNA expression and promoter activity in an NF-κB-dependent manner, regulating several target genes of this signalling pathway (Ding et al 2013).…”
Section: Role Of Tert In Proliferation Invasion and Tumourigenesismentioning
confidence: 98%
“…Reduction of mtDNA damage Improvement of mitochondrial function Higher protection from apoptosis Prevention of nuclear DNA damage (Ahmed et al 2008) (Haendeler et al 2009) (Singhapol et al 2013) Cell death Nuclear TERT localization Diminished mtDNA damage Increase cell survival Protection against cellular senescence (Santos et al 2004) (Santos et al 2006) Nuclear TERT localization High DNA damage (Singhapol et al 2013) (Ding et al 2013) (Hu et al 2015) (Park et al 2007) ) ) ) ) (Liu et al 2013c) (Canela et al 2004) Invasion and metastisation TERT pathway selectively induces TERT mRNA expression in −146C > T mutant cells, in which the mutation creates a binding site specific for p52 that interacts with ETS factors ETS1/2 to mediate TERT reactivation (Li et al 2015b). This study also reports that there is an enhanced tumorigenic and proliferative effect due to NF-κB activation by the increase of telomerase activity dependent on the existence of −146C > T mutation (Li et al 2015b).…”
Section: Functional Effects Of Tert Promoter Mutations In Tumours Andmentioning
confidence: 99%
“…In particular, the authors demonstrated that both hTERT and its catalytic mutant hTERT K626A, which lacks reverse transcriptase activity, could activate NF-kBmediated transcription and regulate the expression of several NF-kB target genes to similar extents (26). Furthermore, overexpression of hTERT or hTERT K626A promoted the nuclear accumulation of NF-kB p65 as well as p65 DNA binding at both basal and TNF-a-induced states (26). These data reiterate the notion that telomerase can function as a transcriptional modulator of the NF-kB signaling cascade in a fashion distinct from its activity at telomeres.…”
Section: Noncanonical Functions Of Telomerase That Intersect With Sigmentioning
confidence: 99%
“…NF-κB p65 modulates hTERT expression and nuclear translocation from cytoplasm in tumor cells (32,33), and hTERT has been shown to contribute to cancer development and progression as a transcriptional modulator of the NF-κB signaling pathway in a manner independent of telomerase activity (7,8). In the present study, we speculated that the C197 interrupts the forward feedback between hTERT and NF-κB signaling pathway which contributes to the antitumor effect of C197.…”
Section: Discussionmentioning
confidence: 73%
“…However, telomerase is reactivated in vast majority of human cancer cells (5) and plays a critical role in the progression of human cancer (6). Recently telomerase has been found to exert extra-telomeric effects via the modulation of NF-κB (7,8) and Wnt/β-catenin signaling pathways (9,10). These non-canonical functions are associated with the development and progression of human cancer.…”
Section: Introductionmentioning
confidence: 99%